(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
An increasing number of educational institutions in the study process uses one of the e-learning systems. Consequently, more and more students are offered learning materials in electronic format. E-materials in distance learning and e-learning is one of the most important elements, therefore much attention and enough time should be paid for their development. There are a number of studies on e-learning quality, where criteria of quality are discussed in the context of chosen e-learning environment and the process of implementation. This article examines only the quality of e-material. The aim was to find a way to reduce the effort and time of electronic learning material quality evaluation. The study used content analysis by summarizing the most important factors influencing the quality for teaching materials. Based on the quality criteria mentioned in the literature and personal experience, a criterion, which affects quality of e-learning material, were summarized and grouped. The criteria were grouped into four groups resulting from didactic, media, usability and formal quality. Quality evaluation is performed by using one of the methods used in software engineering - checklist. Based on the identified quality criteria a checklist was established. In order to facilitate the evaluation process a web-based tool is offered. The tool includes a defined checklist with assessment rating scale and three levels of impact. Evaluation of material quality is shown in the terms of percentage. After testing the tool, it could be used for course developers, program managers or other persons involved in evaluation process of e-learning resources.